PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI VIDEO SCRIBE PADA MATERI LISTRIK STATIS DI SMA - M. Andriansyah M. Andriansyah; M. Rahmad M. Rahmad; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The 21st century is a century filled with advances in information andcommunication technology. Therefore, science is also developing rapidly following thechanges that occur. The development of science and technology, especially in the field ofelectronics, which is supported by various features and applications, can become aninnovation in the manufacture of educational media. One of the innovations in developinglearning media is using the Video Scribe application. This research aims to produce a validlearning media and can be used in the teaching and learning process on Static Electricitymaterial in high school. This type of research uses the ADDIE model. The ADDIE modelconsists of five steps, namely analysis, design, development, implementation, and evaluation.However, in this research, the ADDIE model is only used until the development step. Thisresearch uses a validation sheet as a research instrument that is given to the validation teamwhich opens three validators who are experts in their fields. The results showed that thelearning media based on the Video Scribe application got an average validation score of 4.4which was included in the Valid validation criteria. Thus, learning media based on the VideoScribe application is suitable for use as a learning medium by teachers and this learningmedia can help students understand Electrical Statistics material in high school.Key word: Applications Video Scribe, Static Electricity, Learning Media, Learning Physics